Are We Speaking the Same Language? Communicating Diagnostic Probability in the Radiology Report - Grant, Matthew D; O'Reilly, Corey R; Ladner, Joshua R; Mack, Lisa D; McGrain, Andrew H; Colburn, Zachary T; Boldt, Brian M (American journal of roentgenology (1976), 2021)
The purpose of this study was to evaluate the level of agreement in diagnostic probability for selected phrases among radiologists and emergency medicine (EM) physicians. A survey was distributed to the radiologists and EM physicians at our academic institution. Respondents selected the degree of diagnostic probability they believe was conveyed by 18 commonly used phrases chosen from studies in the radiology literature. Potential responses for the degree of diagnostic probability were < 10%, ≈ 25%, ≈ 50%, ≈ 75%, and > 90%. Seventy-eight percent (28/36) of EM residents and 56% (14/25) of EM attending physicians (combined fellows and attending physicians) completed the survey; 83% (15/18) of radiology residents and 81% (17/21) of radiology attending physicians completed the survey. There was a high degree of shared understanding for most phrases between the departments except for the phrase "compatible with," which was associated with a higher degree of diagnostic probability by radiologists than by EM physicians ( = .02). Although no term was significantly more specific than any other within the ≈ 50% category or below, "most likely" and "diagnostic of" were significantly more specific than other terms in the ≈ 75% and > 90% categories, respectively. The results of this study show a high degree of shared understanding between radiologists and EM physicians for most of the phrases (17/18) in the survey. The only phrase that showed a significant difference was "compatible with." These results can be used to generate diagnostic probability groups with suggested phrases that can be used when creating radiology reports, thereby improving communication with the emergency department.